2011
DOI: 10.1002/mrm.23011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantification of myocardial lipid content in humans using single breath‐hold 1H MRS at 3 Tesla

Abstract: A rapid, proton magnetic resonance spectroscopy method to evaluate human myocardial lipid levels in a single breath-hold at 3 T using a commercial whole-body system is presented. During a 10 s breath-hold, water unsuppressed and suppressed spectra were acquired by two phased array coils using a short-echo time spectroscopic stimulated echo (STEAM) sequence electrocardiogram-triggered to mid-diastole. Lipid-to-water ratios were obtained in the septum of 15 healthy volunteers, (0.46 ± 0.19)%. These results agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 31 publications
5
80
0
Order By: Relevance
“…Spectra were analyzed with MATLAB and the AMARES algorithm included in the jMRUI package 4, as described previously. 10 An example of a proton MRS cardiac spectrum is shown in Figure 1C. Previous studies in our department have demonstrated good reproducibility with this single breath-hold method, with a 19% coefficient of variance.…”
Section: Body Mass and Metabolic Marker Assessmentsmentioning
confidence: 70%
See 2 more Smart Citations
“…Spectra were analyzed with MATLAB and the AMARES algorithm included in the jMRUI package 4, as described previously. 10 An example of a proton MRS cardiac spectrum is shown in Figure 1C. Previous studies in our department have demonstrated good reproducibility with this single breath-hold method, with a 19% coefficient of variance.…”
Section: Body Mass and Metabolic Marker Assessmentsmentioning
confidence: 70%
“…The 1 H-MRS sequence was based on a conventional stimulated echo-acquisition mode sequence that was modified to achieve a short echo time of 10 ms, as described previously. 10 A voxel, or area of interest, was placed in a midventricular slice in the interventricular septum of a short-axis image ( Figure 1). Cardiac gated spectra were acquired as described previously.…”
Section: Body Mass and Metabolic Marker Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous 1 H NMR studies, spectra were acquired using cardiac gating with a trigger delay of 500 to 600 ms from the R wave to ensure acquisition during diastasis. 16,17 Acquisitions were from 4 averages with 4 seconds of recovery between acquisitions within a single breath hold using a point-resolved spectroscopy pulse sequence with dimensions of 10×30×30 mm centered on the ventricular septum (TE 1 =10 ms and TE 2 =14 ms). 18,19 The 4 seconds of recovery between acquisitions limited the potential T 1 -weighting of the water reference signal by allowing >97% recovery of the signal.…”
Section: Mrimentioning
confidence: 99%
“…One must be aware of the potential increase of the water peak by gadolinium-based contrast agents when applying short echo times [24]. Upcoming ultra-fast 1 H-MRS sequences will enable time-saving spectroscopic measurements in patients even prior to i. v. contrast administration [25]. When performing our repetitive 1 H-MRS measurements to achieve data about the technical stability of the method, volunteers were not unloaded from the scanner bay between the different scans and the voxel position was neither changed nor adjusted between the measurements.…”
Section: Technical Stability Of 1 H-mrsmentioning
confidence: 99%